1997
DOI: 10.1063/1.364099
|View full text |Cite
|
Sign up to set email alerts
|

Size-distribution and annealing behavior of end-of-range dislocation loops in silicon-implanted silicon

Abstract: Articles you may be interested in Effects of end-of-range dislocation loops on transient enhanced diffusion of indium implanted in siliconA study of end-of-range ͑EOR͒ dislocation loops in silicon implanted with 50 keV 10 16 Si/cm 2 was carried out by using transmission electron microscopy. Two kinds of post-implantation anneals were performed, furnace anneals at 850°C and rapid thermal anneals at 1000°C. We observed the ripening for two types of EOR dislocation loops. They were faulted Frank dislocation loops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…Both of these results are consistent with the experimental observation that self-interstitial clusters eventually tend to coarsen into FDLs and then PDLs under most anneal-ing conditions. 3,[24][25][26][27][28][29] On the other hand, the absence of ͕100͖ planar defects in silicon wafer annealing experiments cannot be explained on the basis of simple energetics as these are found to possess formation energies that are very similar to the various configurations of ͕113͖ defects. For example, Goss 5 employed DFT within the local density approximation to compute the formation energies of infinite ͕100͖ and ͕113͖ defects, and found that the ͕100͖ defect was in fact slightly favored over the ͕113͖.…”
Section: Formation Thermodynamics For Self-interstitial Clusters-prevmentioning
confidence: 99%
“…Both of these results are consistent with the experimental observation that self-interstitial clusters eventually tend to coarsen into FDLs and then PDLs under most anneal-ing conditions. 3,[24][25][26][27][28][29] On the other hand, the absence of ͕100͖ planar defects in silicon wafer annealing experiments cannot be explained on the basis of simple energetics as these are found to possess formation energies that are very similar to the various configurations of ͕113͖ defects. For example, Goss 5 employed DFT within the local density approximation to compute the formation energies of infinite ͕100͖ and ͕113͖ defects, and found that the ͕100͖ defect was in fact slightly favored over the ͕113͖.…”
Section: Formation Thermodynamics For Self-interstitial Clusters-prevmentioning
confidence: 99%
“…28,31,36 The most common ͕111͖ planar defects observed in implanted silicon are the Frank partial dislocation loops ͑FDL͒ and the perfect dislocation loops ͑PDL͒. [19][20][21] Both planar defects are surrounded by dislocation loops while the Frank partials also include a stacking-fault comprised of two additional ͑111͒ planes of atoms. Under TEM, these defects often appear as either filled ͑Frank partial͒ or open ͑perfect͒ ovalshaped structures.…”
Section: A Brief Overview Of Observed Self-interstitial Cluster Morphmentioning
confidence: 99%
“…Evidence for this type of coarsening behavior has in fact been observed in previous experiments. 20 Generally, the shape of the displacement field around a circular dislocation loop is strongly influenced by the orientation of the Burgers vector. 57,58 For both the FDL and PDL defects, the Burgers vectors have significant components normal to the plane of the loop; these are a / 3͗111͘ ͑i.e., pure edge dislocation͒ and a / 2͗110͘, respectively, where a is the lattice parameter.…”
Section: Direct MD Simulation Of Self-interstitial Aggregation-ementioning
confidence: 99%
See 1 more Smart Citation
“…This evolution model is consistent with the observed thermal evolution of varying defect structure with the temperature and the duration of annealing. 2,[15][16][17][18][19] …”
Section: Implications For Growthmentioning
confidence: 99%